If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(1 + -2m + n) = 0 (1 * -7 + -2m * -7 + n * -7) = 0 (-7 + 14m + -7n) = 0 Solving -7 + 14m + -7n = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 14m + 7 + -7n = 0 + 7 Reorder the terms: -7 + 7 + 14m + -7n = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 14m + -7n = 0 + 7 14m + -7n = 0 + 7 Combine like terms: 0 + 7 = 7 14m + -7n = 7 Add '7n' to each side of the equation. 14m + -7n + 7n = 7 + 7n Combine like terms: -7n + 7n = 0 14m + 0 = 7 + 7n 14m = 7 + 7n Divide each side by '14'. m = 0.5 + 0.5n Simplifying m = 0.5 + 0.5n
| 2(x+5)=4-2(7+x) | | 2x+(x-5)=55 | | 15x^2y-35xy-20x= | | (9x-7)(5x+9)=0 | | 6y^2-10y+3=0 | | 17-(6x+3)= | | 12x^5-19x^3+11x^2= | | 35-5b=0 | | 7(x+4m+3)= | | -9b-1+18+4b= | | z-24=9 | | a=3600-0.8y | | 7(x-3)=4x+3(x-8) | | 6(3-4x)=6(4-4x) | | 5=x+-1 | | 5(x+9)+3=8x-3(x-6) | | 5(2x+2)=3(3x-1)+x | | .33(6p+9)-(p+5)= | | 7mx^2+31m+12=0 | | 1=19-4y | | 4(v-4)-6=-7(-2v+1)-v | | 11x^2+2x+16+(-2x^2)+x+-2= | | 15-(2x+7)= | | -9(5y+3)= | | 12x+10=130 | | u-u+3u-3u+3u=6 | | 7x+6=5x-(3-2x)+9 | | -2(c-5)+3c=4(265-c) | | 7x-20+-10x=11 | | x^2+1.78x^2=3025 | | x+6x^2=16 | | 3.64=x/8 |